Analysis of the role of school leaders in motivating teacher performance (case study at SDN Warungbambu I Karawang) - Noni Febriyanti; Budi Rismayadi; Neni Sumarni (Trigin Publisher, 2022)
The purpose of this study was to determine the role of leaders in motivating teachers to have high performance. This study uses qualitative methods with data triangulation techniques, technical triangulation and source triangulation. Based on the results of the study, it was found that the principal as a leader has provided optimal motivation to teachers. Leaders have done planning, monitoring and evaluation so that motivation is increasingly encouraged. Innovation and creativity from teachers can also be done because the leader as a manager role has been applied at SDN Warungbambu I. The involvement of leaders as part of the organization is very high in supporting the performance of teachers and school staff.